Решение задач неустойчивости с использованием метода дополнительных функций - Ковалев, А.М. (Видавничий дім "Академперіодика" НАН України, 2009)
Дослiджено задачу стiйкостi нульового розв’язку автономної системи диференцiальних рiвнянь. Встановлено теорему про побудову функцiї зi знаковизначеною похiдною або зi знакосталою похiдною, множина обернення якої в нуль є iнварiантною. Доведено теорему про нестiйкiсть у випадку iснування знакосталої похiдної. Розглянуто iлюстративнi приклади. The problem of stability for the zero solution of an autonomous system of differential equations is considered. A theorem concerning the construction of a function with a derivative of fixed sign or a derivative of constant signs such that the set of its zero values is invariant is obtained. An instability theorem for the case of the existence of the derivative of constant signs is proved. Illustrative examples are considered.